Comparison of data-driven identified hypertension-protective dietary patterns among Chinese adults: based on a nationwide study. - Yang, Yuxiang; Piao, Wei; Cai, Shuya; Huang, Kun; Yuan, Changzheng; Cheng, Xue; Zhang, Ling; Li, Yuge; Zhao, Liyun; Yu, Dongmei (European Journal of Nutrition, 2023)
Purpose: Diet pattern (DP) is a key modifiable and cost-effective factor in hypertension (HTN) management. The current study aimed to identify and compare the hypertension-protective DPs among Chinese adults. Methods: 52,648 participants aged over 18 years were included from China Nutrition and Health Surveillance (CNHS) 2015–2017. Reduced rank regression (RRR) and partial least square regression (PLS) was applied to identify the DPs. Multivariable-adjusted logistic regression was used to assess the association between the DPs and HTN. Results: DPs derived by RRR and PLS were both featured by higher consumption of fresh vegetables and fruits, mushrooms and edible fungi, seaweeds, soybeans and related products, mixed legumes, dairy products, fresh eggs, and lower of refined grain consumption. Compared to the lowest quintile, participants in the highest quintile had lower odds of HTN (RRR-DP: OR = 0.77, 95% CI = 0.72–0.83; PLS-DP: OR = 0.76, 95% CI = 0.71–0.82; all p < 0.0001). Simplified DP scores were observed the same protective tendencies (Simplified RRR-DP: OR = 0.81, 95% CI = 0.75–0.87; Simplified PLS-DP: OR = 0.79, 95% CI = 0.74–0.85; all p < 0.0001) and showed effective extrapolation in subgroups defined by gender, age, location, lifestyle, and different metabolic conditions. Conclusions: The identified DPs had high conformity with East Asian dietary habits, and significantly negative associations with HTN among Chinese adults. The simplified DP technique also indicated the potential for improving the extrapolation of the results of DP analysis related to HTN.